2018
DOI: 10.1177/0275074018804662
|View full text |Cite
|
Sign up to set email alerts
|

Are Federal Child Care Programs Sufficient for Employee Retention? Critical Examination From a Gendered Perspective

Abstract: The federal government utilizes diversity management and inclusive organizational practices as principal strategies to achieve higher retention of diverse employees. Child care programs are one of the most important diversity management initiatives to enhance employees’ work–life balance and achieve higher retention. However, existing literature suggests that due to gender norms, child care responsibilities and child care programs have different implications for mothers-in-workforce as compared with fathers-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 90 publications
(221 reference statements)
2
19
0
Order By: Relevance
“…Workplace diversity and inclusion practices have the potential to mitigate workplace discrimination, level the playing field, and improve employment outcomes for employees with disabilities (Chordiya, 2019;Chrobot-Mason & Thomas, 2002;Enayati et al, 2019;Li et al, 2017;Shore et al, 2011). Therefore, consistent with existing literature, the present study utilizes Brewer's (1991) optimal distinctiveness theory (ODT) to focus on elements of organizational inclusion that are expected to optimally satisfy needs of belongingness and uniqueness for employees without disabilities and employees with disabilities.…”
Section: Diversity and Inclusion For Individuals With Disabilitiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Workplace diversity and inclusion practices have the potential to mitigate workplace discrimination, level the playing field, and improve employment outcomes for employees with disabilities (Chordiya, 2019;Chrobot-Mason & Thomas, 2002;Enayati et al, 2019;Li et al, 2017;Shore et al, 2011). Therefore, consistent with existing literature, the present study utilizes Brewer's (1991) optimal distinctiveness theory (ODT) to focus on elements of organizational inclusion that are expected to optimally satisfy needs of belongingness and uniqueness for employees without disabilities and employees with disabilities.…”
Section: Diversity and Inclusion For Individuals With Disabilitiesmentioning
confidence: 86%
“…Therefore, consistent with existing literature, the present study utilizes Brewer's (1991) optimal distinctiveness theory (ODT) to focus on elements of organizational inclusion that are expected to optimally satisfy needs of belongingness and uniqueness for employees without disabilities and employees with disabilities. These are: a) fairness, b) openness to diversity, c) empowerment, d) supportiveness, and e) cooperativeness (Daya, 2014;Detert & Burris, 2007;Chordiya, 2019;Nair & Vohra, 2015;Nembhard & Edmondson, 2006;Sabharwal, 2014; The U.S. Office of Personnel Management, 2015; Vohra et al, 2015). The theoretical framework is depicted in Figure 1.…”
Section: Diversity and Inclusion For Individuals With Disabilitiesmentioning
confidence: 99%
“…Relatedly, scholars are beginning to pool FEVS across years to examine the issue of agency segregation (e.g., Chordiya, 2019; Oberfield, 2014; Sabharwal, 2015). Research finds that women are traditionally segregated into “female type” agencies (Alkadry & Tower, 2006) and have greater representation in redistributive agencies than distributive or regulatory agencies (Guy & Newman, 2004; Kelly & Newman, 2001; Newman, 1994), but little is known about the potential agency segregation of women from racially underrepresented groups.…”
Section: Discussionmentioning
confidence: 99%
“…Attaining a diverse, qualified workforce is one of the cornerstones of the merit-based civil service” (Federal Register, 2011). In light of calls to examine inclusion (Chordiya, 2019; Sabharwal, 2014; Sabharwal, Levine, & D’Agostino, 2018) and the rise in diversity, inclusion, and equity initiatives (Gooden, 2017), we examine feelings of inclusion among women. Do women from racially underrepresented groups have unique experiences that shape their perceptions of inclusion across different dimensions of inclusion, including fairness, openness, cooperation, support, and empowerment?…”
mentioning
confidence: 99%
“…Madera et al (2011) found that employees are more satisfied and less intent on leaving the organization when they are provided with effective diversity training at the workplace. Diversity training increases the value of the workforce and obligates them to stay with the organization (Chordiya, 2019).…”
Section: Effectiveness Of Diversity Training Affective Commitment and Outcomesmentioning
confidence: 99%